Table of Content - - (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content:1. The future roles of school principals in light of the trend towards a knowledge societyMs. Rimah Mudawi Mansour2. The tracking of the development and spread of Covid 19 pandemic in the territory of the Taza Province / MoroccoDr. Abdelouahed Bouberria, Dr. Abdelhafid Hammimi, Dr. Mohammed Abahrour, Dr. Mohammed Errafik3. The Impact of Advertising Campaigns on Consumers’ Purchasing Decision in Delivery Application A Field Study on Grocery Delivery App in Saudi ArabiaMs. Wasaef Ali Bakhashwain, Ms. Lara Zainalabdien Serri, Co-Prof. Mohamed Gad Elmawla Owies4. The Relation of Governance Principles with Job Satisfaction with the Employees of the Ministry of Education, Sultanate of OmanDr. Mouza Said Al-Kharusi5. The emergence of modern intellectual Currents: The Aqeeqah feast between the permissible and the forbidden in northern Togo “Cinkasse”Mr. Ibrahim Youssif
Keywords: Arab Journal of Sciences & Research Publishing